The Theory of Knowledge Spillover Entrepreneurship* - Audretsch, David B.; Keilbach, Max (Journal of Management Studies, 2007)
abstract The prevailing theories of entrepreneurship have typically revolved around the ability of individuals to recognize opportunities and then to act on them by starting a new venture. This has generated a literature asking why entrepreneurial behaviour varies across individuals with different characteristics while implicitly holding constant the external context in which the individual finds herself. Thus, where the opportunities come from, or the source of entrepreneurial opportunities, is also implicitly taken as given. By contrast, in this paper an important source of entrepreneurial opportunities is identified – knowledge and ideas created in an incumbent organization. By commercializing knowledge that otherwise would remain uncommercialized through the start‐up of a new venture, entrepreneurship serves as a conduit of knowledge spillovers. According to the theory of knowledge spillover entrepreneurship, a context with more knowledge will generate more entrepreneurial opportunities. By contrast, a context with less knowledge will generate fewer entrepreneurial opportunities. Based on a data set linking entrepreneurship to the knowledge context, empirical evidence is provided that is consistent with the proposition that entrepreneurial opportunities are not exogenous but rather systematically created by investments in knowledge by incumbent organizations.